Comparison of nutritional status between patients from urban area with rural area undergoing hemodialysis in Kushtia district, Bangladesh: a cross-sectional study (Asian Journal of Medical and Biological Research, 2017)
Malnutrition is a common problem in patients with end stage kidney disease (ESKD) undergoing hemodialysis that increases morbidity and mortality rate in Bangladesh. The main objective of this cross sectional study was carried out to compare the nutritional status between urban patients with rural patients undergoing hemodialysis. End-stage renal-failure outpatients who underwent hemodialysis were recruited from Sono Hospital Limited, Kushtia, Bangladesh. Direct method of nutritional assessment including anthropometric measurement, biochemical measurement, clinical assessment and dietary method was carried out. Socio economic data were also collected. The result reveals that 69.0% of the total participants were male and 31.0% were female. The mean age of male was 46.10±13.23 years and that of female was 43.11±16.47 years. Among 142 cases 50.0% were from urban area and 50.0% were from rural area. 53.5% of the total participants were economically satisfied and 46.5% were non-satisfied. 76.3% of high socioeconomic group consisted of urban area and 23.7% consisted of rural area. Again 19.7% of low socioeconomic group consisted of urban area and 80.3% consisted of rural area. According to WHO classification for BMI 15.5% had BMI below 18.5kg/m2 in urban and 18.3% had BMI below 18.5kg/m2 in rural area. Of the total participants 97.2% were anemic, 66.9% had anorexia, 69.7% had depression, 63.4% had nausea, 58.5% had vomiting, 30.3% had heartburn, 47.2% had constipation, 38.0% had dizziness, 19.7% had chest pain, 5.6% had dysphagia, 34.5% had fatigue, 48.6% had headache, 26.1% had diarrhea, 50.7% had pruritus and 13.4% had shortness of breath. Mean±SD hemoglobin level of urban participants was 8.37±1.46 and that of rural participants was 8.12±1.85. The result shows that malnutrition was more prevalent among rural hemodialysis patients than that of urban. The cause of malnutrition was related to low socioeconomic condition and inadequate nutrient intake.Asian J. Med. Biol. Res. December 2016, 2(4): 603-610